The Study of Certain Types of Natural Fibers Determination of Their Properties by Organoleptic and Laboratory Methods (Eurasian Research Bulletin, 2022)
This article discusses the study of certain types of natural fibers, the determination of their properties by organoleptic and laboratory methods - distinctive features in the study of the structure of natural fibers using light and a microscope.